Analisis Efisiensi Alokatif Faktor Produksi pada Usahatani Jagung di Desa Lairuru Kecamatan Umalulu Kabupaten Sumba Timur - Sir, Omri Waang; Wadu, Junaedin (Universitas Galuh, 2024)
This research aims to analyze the factors that influence corn production and the allocative efficiency of corn production in Lairuru Village, Umalulu District, East Sumba Regency. The population in this study were all corn farmers in Lairuru Village. The number of samples was determined using the Slovin method with an error tolerance level of 10%, so the sample size was determined at 68 people. The data analysis method that will be used in this research uses multiple linear regression analysis to analyze the influence of production factors on the amount of production, and efficiency analysis to analyze the level of allocative efficiency in the use of production factors in corn farming in Lairuru Village. The results of the analysis of the influence of production input factors on corn production in Lairuru Village explain that the factors of seeds, pesticides and labor have a significant influence on the amount of production. Meanwhile, land area, urea and NPK fertilizer factors do not have a significant influence on the amount of production. The results of the efficiency analysis explain that the use of land area, seeds, urea fertilizer, NPK fertilizer, pesticides and labor in corn farming in Lairuru Village is declared inefficient.